Rancang Bangun Remainder Kegiatan Pegawai di Kantor PPAT Notari Mangtas Nasution S.H Berbasis Android - Ayyuna, Ifrah; Inayah, Anggita Dwi; Nadilla, Nur; Dedi, Muhammad (Jurnal Ilmiah Sains dan Teknologi, 2024)
The development of technology today plays a very important role in people's lives. Technology that has developed from time to time is expected to be a supporting tool to help manage and solve problems in the Mangtas Notary office. In this office, when analyzing and collecting data, a problem was found, namely that the employee activity system in the Mangatas Notary office still uses a manual system that has not been digitized. Therefore, the Android-based employee activity reminder app in Mangatas Notary Office is designed to help make it easier to convey information faster and more accurately. This study uses a data collection method through interviews and literature studies, while the system development method uses the Waterfall Method. The purpose of this application is to provide information about every activity that employees will do. This application was created to influence the progress at the Mangatas Notary Office in Technology Development